2021
DOI: 10.1080/17457300.2021.1928234
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship between impaired driving and past crash involvement in Europe: Insights from the ESRA study

Abstract: Driving under the influence of alcohol, drugs and fatigue are all important factors of crash causation. Exploring the link between driver attitudes and crash involvement provides understanding on these important issues. To that end, questionnaire answers of car drivers disclosing their attitudes on the impacts of driving under the influence of alcohol, drugs and fatigue, and their relationship with past crash involvement as car drivers were analysed. A two-step approach is adopted: Principal Component Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
5
0
2
Order By: Relevance
“…It is well known that this kind of data are often less accurate and include inherent biases (Backer-Grøndahl & Sagberg, 2011). The bias may be from a misunderstanding of the question to desirability or recall bias (Ziakopoulos et al, 2021a). However, because most of the answers are drawn from a time period of a month recall error can reasonably be assumed to be limited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that this kind of data are often less accurate and include inherent biases (Backer-Grøndahl & Sagberg, 2011). The bias may be from a misunderstanding of the question to desirability or recall bias (Ziakopoulos et al, 2021a). However, because most of the answers are drawn from a time period of a month recall error can reasonably be assumed to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Goldenbeld et al (2020) found that in Europe drug driving was less frequently reported than drinking and driving, while in other continents it was reported as frequently. Ziakopoulos et al (2021a) examined several unsafe powered-twowheeler rider behaviours using ESRA2 data and found that they are correlated with a number of causal factors and with each other.…”
Section: The Esra Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [20] used EFA to identify the most suitable factor structure for drivers in New Zealand and explored the correlations between factor outcomes and crash involvement. Ref.…”
Section: Introduction To Efa and Auditmentioning
confidence: 99%
“…According to the World Health Organization (WHO), 5% to 35% of the total number of deaths in road traffic crashes come from driving under the influence of alcohol ( 7 ). According to the European Survey of Road Users’ Safety Attitudes (ESRA) project, alcohol contributed to the occurrence of 20% to 25% of the total number of road traffic crashes with fatalities at the European level ( 8 ). In addition, as stated in the Social Attitudes to Road Traffic Risk in Europe (SARTRE4) project, driving under the influence of alcohol is a factor in the occurrence of one out of four road traffic crashes ( 9 ).…”
mentioning
confidence: 99%